Создание Т-образного затвора в малошумящих полевых СВЧ-транзисторах - Bosiy, V. I.; Korzhinskiy, F. I.; Semashko, E. M.; Sereda, I. V.; Sereda, L. D.; Tkachenko, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
The process of forming T-shaped gates in low-noise field-effect transistors for millimeter and submillimeter wavelength ranges has been investigated. A technological scheme for gate formation is proposed, based on electron-beam exposure of a three-layer resist structure consisting of two layers of electron resist separated by a thin metal layer. Experimental transistor samples with T-shaped gates have been fabricated, featuring a gate height of 1.1 μm, a bottom part length of 0.15 μm, and a top part length of 0.8–1.0 μm.